EFFICIENCY OF MANAGEMENT AU AGROFIRM «ISCRA» - Войцеховский, Владимир (SWorldJournal, 2020)
The article analyzes the profitability of growing different crops in the forest-steppe zone of Ukraine. It was established that the profitability of the economy is 36.2%. Corn for silage and herbs have a low profitability, and the highest profitability wa